Evaluasi Sistem Pemungutan dan Penerimaan Pajak Bumi dan Bangunan Pada Badan Pendapatan Daerah Kabupaten Merauke - Hesty Tambajong; Maryani Febry Mengko; Syahrabudin Husein Enala; Hubertus Oja (PAPSEL Research and Consulting, 2024)
The aim of this research is to evaluate the PBB P2 acceptance procedures at the Merauke Regency Bapenda based on the government's internal control system policy. The type of research used is qualitative research with a descriptive approach and data obtained through interviews and documentation. The results of the research show that internal control at the Regional Revenue Agency of Merauke Regency in the procedures for receiving Rural and Urban Land and Building Tax is implemented well because there are several components that are optimal, namely in the control environment where the registration, data collection and functional human resources are there so that there are multiple tasks. , risk assessment where the Merauke Regency Bapenda is still carrying out passive data collection due to a lack of functional assessors, and a lack of monitoring of PBB P2 collection which has not fully carried out direct monitoring of taxpayers so that there are still many taxpayers who have not carried out their obligations in paying PBB P2. In other cases, officers have not implemented the SOP in implementing the PBB P2 collection system. It cannot be denied that this is very important for tax officers and taxpayers to follow in order to ensure that the PBB collection process runs smoothly and transparently in accordance with the provisions of the applicable laws and regulations.